2021
DOI: 10.1038/s41598-021-02950-4
|View full text |Cite
|
Sign up to set email alerts
|

A 52 weeks dupilumab treatment for moderate to severe atopic dermatitis in Korea: long-term efficacy and safety in real world

Abstract: Previously, we have reported short term effectiveness and safety of dupilumab in Korea. In this study, we are trying to report the long-term effectiveness and safety of dupilumab in Korea. Ninety-nine patients with moderate to severe AD were analyzed. They were evaluated using Eczema Area and Severity Index (EASI), Numerical Rating Scale (NRS), Patient Oriented Eczema Measure (POEM), and Dermatology Quality of Life Index (DLQI) at baseline, week 16, 32 and 52. Efficacy outcomes showed higher improvement at 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
4
17
0
Order By: Relevance
“…Thirty‐five per cent of our patients reported AEs in the 2‐year follow‐up, which is similar to 32–35% in three studies with 1 year follow‐up from Italy and Portugal, 13–15 but lower than 61% observed in a Czech study with 2‐year follow‐up 7 . One in four patients reported conjunctivitis, which is comparable to other studies with long follow‐up, 5,6,13,15,16 while also markedly higher than selected studies with up to 2‐year follow‐up 9,14,17 . Differences in reporting patterns and specific focus on conjunctivitis and preventive initiatives with artificial tears might explain the differences.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thirty‐five per cent of our patients reported AEs in the 2‐year follow‐up, which is similar to 32–35% in three studies with 1 year follow‐up from Italy and Portugal, 13–15 but lower than 61% observed in a Czech study with 2‐year follow‐up 7 . One in four patients reported conjunctivitis, which is comparable to other studies with long follow‐up, 5,6,13,15,16 while also markedly higher than selected studies with up to 2‐year follow‐up 9,14,17 . Differences in reporting patterns and specific focus on conjunctivitis and preventive initiatives with artificial tears might explain the differences.…”
Section: Discussionsupporting
confidence: 75%
“…Women further tended to achieve EASI 75 and EASI 90 more often than men in our study, confirming previous findings. 17,31 We observed that patients over 60 years of age had slightly delayed treatment response at week 4. However, better treatment response at week 16 support the results from Patruno et al 32 Patients with current asthma had a delayed and lower effectiveness response than those without comorbid asthma, probably explained by asthmatic AD patients having worse baseline AD.…”
Section: Effectivenessmentioning
confidence: 78%
See 1 more Smart Citation
“…Recently, dupilumab has successfully been used to treat severe atopic dermatitis (AD). 1,2 However, it was not always effective as expected and adverse events such as facial erythema also occurred. 3 In that cases, previous studies introduced the combination therapy of dupilumab and systemic immunosuppressants to improve efficacy and mitigate the side effects.…”
mentioning
confidence: 88%
“…In our previous study into real-world patients with moderate to severe AD on dupilumab, it showed long-term safety and efficacy, in which about 60% of patients achieved a 75% improvement in EASI score (EASI-75) after 16 weeks. 5,6 the contrary, the other 40% of patients did not achieve EASI-75, and several adverse events including conjunctivitis, injection site reaction, and herpes simplex virus infection were observed. 6 In this regard, the need for an alternative to dupilumab has been raised for such patients.…”
mentioning
confidence: 96%